ANALISIS PELAKSANAAN SISTEM PENGELUARAN KAS PADA DINAS PEKERJAAN UMUM DAN PENATAAN RUANG KABUPATEN SIKKA - Pipiet Niken Aurelia; Siktania Maria Dilliana; Jeinita Fransiska Jaro (Jurnal Accounting UNIPA, 2022)
The purpose of this study was to determine the implementation of the cash disbursement system at the Public Works and Spatial Planning Office in Sikka Regency. Cash disbursement system is an organization of forms, records and reports created to carry out expenditure activities both by check and cash. The object of this research is the Department of Public Works and Spatial Planning of Sikka Regency. The method used is a qualitative descriptive method that compares data based on observations, interviews and documentation at the research site with Mulyadi's theory and Minister of Home Affairs Regulation No. 13 of 2006. The results of the research show that the implementation of the cash disbursement system at the Public Works and Spatial Planning Department . There is no separation of functions in the implementation of the cash disbursement system, while documents, records and procedures have been carried out quite well. Keywords: Analysis, System Implementation, Cash Expenditures